Oral hygiene practices, dental experiences and dietary habits in school going children - ., Amit; Hooja, Ribhu; Mital, Prachi; Nirwan, Mitakshra (International Journal of Contemporary Pediatrics, 2022)
Background: Prevalence of oral diseases is increasing with growing urbanization and changes in living conditions. Increasing consumption of sugary snacks, chocolates, sugary or aerated drinks are making children prone to develop dental problems. Regular toothbrushing, rinsing mouth with water, use of mouthwashes and inter dental brush or dental floss, a balanced diet and regular visits to dentist are associated with a decreased risk of dental diseases. Objective was to determine the oral hygiene practices, dietary habits and dental experience among children of 3-15 years. Methods: This was a cross-sectional study carried out at a tertiary care center and dental college. Questionnaire was used to determine the dental health practices, dietary habit and dental experiences. Responses of 100 duly filled forms were included and statistically analyzed. Results: 100% of the students brushed their teeth daily with toothpaste. About 53% brushed at least twice daily. 85% children rinsed mouth with water after brushing, 42% rinsed mouth with water after every meal. Adult help required for brushing and habit of eating in between meals snacks were significantly more in children of primary section compared to children of 6th standard onwards. Only 16% children were using mouthwash regularly. 47% children visited dentist for various reason out of which 46.8% visited for routine check-up. Conclusions: In our study 100% children were brushing their teeth at least once a day, 42% were rinsing mouth after every meal. Efforts should be made to promote good oral hygiene habits among children through various educational programs.